A review on surface coating strategies for anti-hygroscopic of high energy oxidizer ammonium dinitramide - Hongyu Yang; Fuyao Chen; Yiwen Hu; Qiangqiang Lu; Lei Xiao; Yinglei Wang; Fengqi Zhao; Wei Jiang; Gazi Hao (Defence Technology, 2024)
Ammonium dinitramide (ADN), which has the advantages of high energy density, no halogen and low characteristic signal, is not only considered as a new high-energy oxidizer that is expected to replace the traditional oxidizer ammonium perchlorate (AP) in solid propellants, but also a good performance explosive in itself. However, due to the strong hygroscopicity of ADN, its application in solid propellants and explosives is greatly limited. Solving the hygroscopicity of ADN is the key to realize the wide application of ADN. In this paper, we systematically review the research progress of anti-hygroscopic strategies of ADN coating. The surface coating methods are focusing on solvent volatilization, solvent-non-solvent, melt crystallization and atomic layer deposition technology. The characteristics of the different methods are compared and analyzed, and the basis for the classification and selection of the coating materials are introduced in detail. In addition, the feasibility of material for surface coating of ADN is evaluated by several compatibility analysis methods. It is highly expected that the liquid phase method (solvent volatilization method, solvent-non-solvent method) would be the promising method for future ADN coating because of its effective, safety and facile operation. Furthermore, polymer materials, are the preferred coating materials due to their high viscosity, easy adhesion, good anti-hygroscopic effect, and heat resistance, which make ADN weak hygroscopicity, less sensitive, easier to preserve and good compatibility.